Investigation and numerical simulation on film cooling performance with an anti-vortex hole design: Influences of diameter ratio. (February 2021) - Zhu, Rui; Lin, Enci; Simon, Terrence; Xie, Gongnan
Abstract: This paper extends the development of film cooling for application to gas turbines. Three diameter ratios of secondary hole to primary hole (0.3, 0.5 and 0.7) are constructed in an anti-vortex hole design. Film cooling effectiveness values and heat transfer coefficients are measured by the Thermochromic Liquid Crystal technique. In-flow temperature fields over downstream planes oriented normal to the main flow are measured by traversing a thermocouple. Numerical simulations are made to compute details of the flow structure to describe underlying mechanisms. Three coolant-to-mainstream blowing ratios (0.5, 1.0 and 1.5) and two coolant-to-mainstream mass flow ratios (3.43% and 5.15%) are tested. The anti-vortex hole design reduces the deleterious effects of the kidney vortex pair generated at the emersion point of the coolant jet into the passage, enlarges the film coverage, and finally improves film cooling effectiveness. The anti-vortex hole with larger secondary holes usually provides higher film cooling effectiveness.